Kamus Indonesia-Gorontalo - Pateda, Mansur (Jakarta : Balai Pustaka, 1991)
Indonesian-Gorontalo dictionary.
Indonesian and Gorontalo.
Publisher stock no.: 3608.
Keywords: Indonesian language -- Dictionaries -- Gorontalo